Swedish people 1955_4 - Hultgren, Sten (Svenska Gallupinstitutet AB, 1986)
Swedish people 1955 is the first part of the first large-scale survey in Sweden attempting to give an objective picture of interests, personalities, opinions, habits and living conditions in Sweden. The second part was made in 1970 (Swedish people 1970). The Swedish Opinion-studies (1979-1985) repeat some of the questions from these studies. Questions about opinions of human behaviour, interests, attitude to alcohol, religion, possesions, social benefits, voting, Swedish conditions, work and trade unions, studies, personal conditions, children´s upbringing and education, parents, membership in different organizations and personal data.

Swedish people 1955 is the first part of the first large-scale survey in Sweden attempting to give an objective picture of interests, personalities, opinions, habits and living conditions in Sweden. The second part was made in 1970 (Swedish people 1970). The Swedish Opinion-studies (1979-1985) repeat some of the questions from these studies. Questions about opinions of human behaviour, interests, attitude to alcohol, religion, possesions, social benefits, voting, Swedish conditions, work and trade unions, studies, personal conditions, children´s upbringing and education, parents, membership in different organizations and personal data.
Svenska folket 1955_4
Keywords: living conditions; levnadsförhållanden; standard of living; levnadsstandard; social behaviour; socialt beteende; social attitudes; sociala attityder; interest (cognitive processes); intresse (kognitiva processer); public opinion polls; opinionsundersökningar; Social behaviour and attitudes; Socialt beteende och attityder; Social Sciences; Samhällsvetenskap